Utilization of Livestock Waste (Cow Manure) and Household Waste (Waste Cooking Oil) as Briquettes to Substitute Alternative Fuels - Noorrahman, Nabil Fariz; Sandriya, Ardi; Paulini, Paulini (Universitas Bengkulu, 2024)
As the global population continues to grow, there is a corresponding increase in energy consumption annually. The need for alternative energy sources is evident in light of the finite reserves of oil. Briquettes are a renewable energy option that can help decrease reliance on oil. Briquettes can be produced through the utilization of organic waste materials. This research was carried out from 19 September to 18 October 2023, at the Faculty of Agriculture, University of Palangka Raya, and the Analytical Laboratory, Muhammadiyah University, Palangka Raya. The aim of this research is to determine the quality of briquettes made using cow dung charcoal and cooking oil as an adhesive. The parameters of this research are water content, ash content, burn rate, and colorific value. This research used a Completely Randomized Design (CRD) model with 4 treatments and each treatment was repeated 5 times so that there were 20 experimental units. The composition of the briquettes consists of (P1) = 90% cow dung and 10% used cooking oil, (P2): 87.5% cow dung and 12.5% ​​used cooking oil, (P3): 85% cow dung and 15% used cooking oil and (P4): 82.5% cow dung and 17.5% ​​used cooking oil. The results of variance analysis showed that the parameters of water content, ash content, burn rate, and colorific value did not show a significant influence between treatments (P>0.05) although there was a trend that P1 and P3 were better than the other treatments. It was concluded that the best quality of briquettes in terms of water content and ash content was in the P1 treatment (Briquettes with a composition of 90% cow dung and 10% used cooking oil), whereas if viewed from the burning rate and calorific value of the best briquettes, it was the P3 treatment (Briquettes with a composition of 85 % cow dung and 15% used cooking oil).